Pamatinės teisės idėjos kaip bendrieji teisės principai ir konstituciniai principai - Šinkūnas, Haroldas; Isokaitė-Valužė, Indrė (Vilnius University Open Series, 2024)
The article aims at the analysis of the general principles of law in the international law and the constitutional law: the general principles of law in the case law of the International Court of Justice and the jurisprudence of the Constitutional Court of the Republic of Lithuania as well as their interplay. The concept of the general principles of law as underlying ideas identifiable in each legal system, as well as their types, functions and specifics are examined. Systematic and comparative research reveals the role of the general principles of law in the international law and the constitutional law of the Republic of Lithuania demonstrating their peculiarities in the said two legal systems, including the extent of coincidence and interrelation. The article emphasizes the significance of the general principles in both legal systems, including their role in construing, creating (developing) and applying law, as well as filling in gaps, recognizes their universality and commonness of their purpose and differences stipulated by the nature of each legal system. The analysis of the case law of the International Court of Justice reflects the discussion on the identification of the general principles of law and their recognition as such in the international law as well as the Court’s creativity in applying and construing them as the general principles of law, while the jurisprudence of the Constitutional Court of the Republic of Lithuania refers to both, the general principles of law and the constitutional principles, both being interconnected – although retaining their autonomy. It is highlighted that the general principles of law, reflecting the essential ideas and fundamental values of law, retain their unique significance despite their possible overlap with or reflection in other principles or rules.